PENGARUH LINGKUNGAN KERJA, KOMITMEN ORGANISASI DAN BUDAYA ORGANISASI TERHADAP EFEKTIVITAS KERJA MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Rizal Yulianto, Mochamad; Saputro, Wahyu; Ubaidillah, Hasan; Nashrullah, Mochamad (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of Work Environment, Organizational Commitment, and Organizational Culture on Work Effectiveness with Organizational Citizenship Behavior as an Intervening Variable at PT. Ilham Hasil Mandiri. This study uses a quantitative approach. The data collection technique is by distributing questionnaires. The population in this study were 150 employees of PT. Ilham Hasil Mandiri. The sample in this study were 60 employees of PT. Ilham Hasil Mandiri. Sampling using propability sampling technique. The analysis technique used in this research is path analysis, using the SmartPLS 3.0 application program. The results of the research conducted prove that the work environment has a significant effect on work effectiveness, organizational commitment has no significant effect on work effectiveness, organizational culture has a significant effect on work effectiveness, the work environment does not have a significant effect on work effectiveness through organizational citizenship behavior, organizational commitment does not significant effect on work effectiveness through organizational citizenship behavior, organizational culture has no significant effect on work effectiveness through organizational citizenship behavior, organizational citizenship behavior has no significant effect on work effectiveness at PT. Ilham Hasil Mandiri.